Compliance-Based Determination of Fatigue Design Curves for Elastomeric Adhesive Joints - Pedro Henrique Evangelista Fernandes; Christof Nagel; Andreas Wulf; Vinicius Carrillo Beber; Bernd Mayer (Eng, 2023)
A compliance-based method for the determination of fatigue design curves for elastomeric adhesive joints is developed and validated. Fatigue experiments are conducted on elastomeric adhesives (a polyurethane and a silane-modified polymer) under different stress ratios (R = 0.1/0.5/−1) and conditions (23 °C/50% r.h. and 40 °C/60% r.h.). The investigation focused on butt and thick adherent shear test joints. Fatigue tests are recorded with cameras to identify the stages of crack initiation and propagation. For each fatigue test, the stiffness and compliance per cycle are calculated until final failure. The proposed method identifies a transition point that distinguishes regions under stable and unstable compliance growth. Fatigue design curves are then built based on the transition point and on the number of cycles to reach different degrees of initial stiffness (90%, 80%, 70% and 60%). The failure ratio, i.e., the lifetime for reaching a given approach divided by the total lifetime, is introduced to evaluate the data in terms of average values and standard deviation. The results indicate that the proposed method can yield fatigue design curves with a high coefficient of determination (accuracy) and high failure ratio (avoiding over-conservative design). Moreover, the method is robust, as the failure ratio for different adhesives, stress ratios, conditions and geometries is highly consistent.